Stock Price Determination at Bank Pembangunan Daerah Jawa Barat (BJB) - Ryan Farezi; Vietha Devia Devia (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
Stock price fluctuations are one of the factors that affect and challenge investors. In addition, investors do not only invest for the sake of short, but also in the long term. Banks are one of the main pillars in Indonesian stocks. It is known that Bank Bjb has a good level of health but until now the share price of bank bjb has decreased considerably since 2017. This study will discuss how the determination of stock prices using the CAMELS method at the West Java Regional Development Bank in 2015 quarter 1- 2023 quarter 4. this research uses quantitative research methods carried out associatively. The data analysis technique used in this article is the Error Corecction Model (ECM) which aims to determine the short-term and long-term relationship between variables. The results showed that in the short-term CAR, and NPL have no influence on stock prices. In the long run CAR, NPM, and ROA affect stock prices. While NPL, LDR, and Interest Rate does not have any influence on stock prices.   Keywords: CAMELS; Error Correction Model (ECM); Stock Price; Financial Performance; Banking Sector